2021
DOI: 10.1016/j.ygeno.2021.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a combined species SNP array for the European seabass (Dicentrarchus labrax) and gilthead seabream (Sparus aurata)

Abstract: SNP arrays are powerful tools for high-resolution studies of the genetic basis of complex traits, facilitating both selective breeding and population genomic research. The European seabass ( Dicentrarchus labrax ) and the gilthead seabream ( Sparus aurata ) are the two most important fish species for Mediterranean aquaculture. While selective breeding programmes increasingly underpin stock supply for this industry, genomic selection is not yet widespread. Genomic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
(76 reference statements)
3
43
0
Order By: Relevance
“…The three reported robust outlier SNPs were found to be significant outliers in multiple genetic clusters of farmed fish populations when contrasted with different genetic clusters of wild populations. This finding supports a scenario of parallel signatures of adaptation of gilthead seabream to the farmed conditions, which remains to be investigated further, for instance, with the use of higher-density SNPs that have been recently developed for gilthead seabream [75]. We also reported on the biological role and function of multiple genes closely linked to the outlier SNPs that may explain the observed divergence, and provide targets for future research in the domestication of gilthead seabream.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The three reported robust outlier SNPs were found to be significant outliers in multiple genetic clusters of farmed fish populations when contrasted with different genetic clusters of wild populations. This finding supports a scenario of parallel signatures of adaptation of gilthead seabream to the farmed conditions, which remains to be investigated further, for instance, with the use of higher-density SNPs that have been recently developed for gilthead seabream [75]. We also reported on the biological role and function of multiple genes closely linked to the outlier SNPs that may explain the observed divergence, and provide targets for future research in the domestication of gilthead seabream.…”
Section: Discussionsupporting
confidence: 81%
“…The fact that we detected three candidate SNPs for domestication in gilthead seabream by screening a relatively low number of 1159 random genomic SNPs suggests potentially strong divergent selection for domestication that, for example, medium-to-high-density SNP screening approaches may be able to elucidate further. To this end, Peñaloza et al recently reported on the development of a 15K SNP chip for gilthead seabream that may be ideally suited for this purpose [75]. Our analysis of the semantic similarity of the genes within 20 Kbps from the three candidate SNPs also managed to recognize some common functional patterns (Figure 5).…”
Section: Assessing the Significance Of Candidate Snps For Domestication In Gilthead Seabreammentioning
confidence: 77%
“…The availability of resources including reference genomes, linkage maps, genotyping arrays, etc., convenes the applicability of the GS along with genome-wide association studies. Not long ago, the reference genome of European sea bass became available (Tine et al, 2014), and very recently, the SNP genotyping Axiom arrays were also developed, which are a part of the public domain now (Griot et al, 2021;Peñaloza et al, 2021). There are several studies on different aquaculture species where quantitative trait loci (QTL) were detected for traits of economic and welfare importance using medium-to high-density SNP arrays.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in private alleles between the Celtic shelf and Portuguese uncovered population structuring not observed using neutral markers (Souche et al, 2015), and indicates the potential for MHC‐I to detect fine‐scale population variation. Markers in the MHC region can be particularly good for showing fine scale differentiation, as changes can accumulate relatively quickly and are affected by local selection (Consuegra et al, 2005), and genome‐wide high‐throughput methods (Griot et al, 2021; Penaloza et al, 2021) can help identify additional markers under selection (Carreras et al, 2017). Our study provides the first detailed analysis of MHC class I in seabass, a species that supports important commercial and sport fisheries, as well as aquaculture.…”
Section: Discussionmentioning
confidence: 99%